System bonus-malus - mierniki tempa zbieżności modelu do stanu stacjonarnego - Śliwka, Piotr (Bonus Malus System - the Measures of Convergence Speed of the Models to the Stationary State, 2006)
Applied measures of quality of the bonus-malus system include stationary distribution in the analitycal structure. This is directly connected with the estimate of convergence rapidity of matrix Pn to ergodic matrix E. A new appraisal of convergence rapidity Pn to E, which depend on multiplicity of the modulus of the second largest eigenvalue in TV norm is proposed in this article. The new appraisal in the case of single eigenvalues of matrix P is more precise than existing in literature, and in the case of multiple eigenvalues does not depend on unessential states of Markov cha
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 403-423